Poverty Alleviation Among the Younger Generation Through the Prevention of Online Gambling and Financial Literacy Based on Communication for Development in East Kotawaringin Regency - Akhmad Jaki (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
Poverty remains a structural challenge in Indonesia, particularly in rural areas of East Kotawaringin Regency, Central Kalimantan. The rapid growth of digital-based online gambling has increased socio-economic vulnerability among young people aged 15–24, especially students and out-of-school youth from low-income households with limited financial literacy. Data from the Central Kalimantan Financial Services Authority (OJK) show that the regional financial literacy index is only 32.73%, well below the national average, increasing exposure to risky financial behavior. This community service program offers a novel participatory approach by integrating Participatory Action Research (PAR) with Communication for Development (C4D). Unlike conventional one-way financial literacy initiatives, the program emphasizes youth empowerment and community-based communication. It is implemented as a six-month intervention in selected villages through three stages: participatory diagnosis, co-creation of financial literacy and online gambling prevention messages, and youth-led digital media campaigns. The program aims to support poverty alleviation by promoting behavioral change, financial resilience, and critical digital awareness among young people, while aligning with the Sustainable Development Goals (SDG 1; SDG 4, and SDG 8) and Indonesia’s National Financial Inclusion Strategy. Strategic partners include the Financial Services Authority (OJK), youth organizations, and local schools. Program impacts are measured through pre–post surveys and focus group discussions, indicating improved financial literacy, increased awareness of online gambling risks, and strengthened youth participation in participatory digital communication. Outputs include digital learning modules, school-based training, and youth-produced educational content